Pengaruh Karakteristik Sistem Akuntansi Manajemen (SAM), Komitmen Organisasi, Dan Ketidakpastian Lingkungan Terhadap Kinerja Manajerial - Desak Putu Febriyanti; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2023)
Managerial performance is a measure of the effective and efficient performance of each organization. The importance of managerial performance in the hospitality industry is to evaluate, analyze and develop management programs. This study aims to determine the characteristics of the Management Accounting System, Organizational Commitment, and Environmental Uncertainty on Managerial Performance at 4-star Hotels in Ubud District.The number of samples used was 99 people with purposive sampling. Data collection using a questionnaire. Data analysis techniques using multiple linear regression tests. The hypothesis test used is the t test. The results showed that the characteristics of the management accounting system (SAM) had a positive and significant effect on managerial performance. Organizational commitment has a positive and significant effect on managerial performance. Environmental uncertainty has a positive and significant effect on managerial performance. It is expected that the Company can increase the relevance of information presented by the management accounting system by improving the data collection and information processing processes. Companies can increase the reliability of information by improving their internal controls. To increase employee satisfaction, managers must have flexibility in carrying out business operations.